Diagnosis and Treatment of Pityriasis Versicolor: A Review of Current Methods and Research Findings - Jasiuk, Adrianna; Wiekiera , Mateusz; Madeja, Natalia; Koziej , Sylwia; Niemczuk , Martyna; Kowalczyk, Emilia (Quality in Sport, 2025)
Pityriasis versicolor is a common, mild skin disease caused by a yeast-like fungus from the Malassezia genus. This fungus naturally inhabits the skin of healthy individuals, but under certain conditions, such as increased sebum production or immunocompromised states, it can lead to the formation of scaly patches that are hypo or hyperpigmented, and sometimes they can be discolored. These lesions typically appear on the torso, neck, or shoulders and vary in size. Over time, they may enlarge. Diagnosis involves a physical examination, mycological testing, and examination under a Wood’s lamp. Treatment consists of topical or systemic antifungal medications. The condition is recurrent. Personal hygiene plays an important role in prevention. The article is a comprehensive review of the available scientific literature on the pathogenesis, clinical picture, diagnosis and treatment of pityriasis versicolor.